Bioequivalence of oral and intravenous carbamazepine formulations in adult patients with epilepsy. (16th May 2015) - Tolbert, Dwain; Cloyd, James; Biton, Victor; Bekersky, Ihor; Walzer, Mark; Wesche, David; Drummond, Rebecca; Lee, Deborah
Summary Objective To evaluate the safety, tolerability, and comparative pharmacokinetics (PK) of intravenous and oral carbamazepine. Methods In this phase 1, open‐label study, adult patients with epilepsy on a stable oral carbamazepine dosage (400–2, 000 mg/day) were converted to intravenous carbamazepine (administered at 70% of the oral dosage). A 28‐day outpatient period preceded an up to 10‐day inpatient period and a 30‐day follow‐up period. Intravenous carbamazepine was administered over 15 or 30 min every 6 h on days 1–7; some patients in the 15‐min group were eligible to receive four 2‐ to 5‐min (rapid) infusions on day 8. Patients underwent blood sampling to determine the area under the concentration–time curve (AUC) for carbamazepine and metabolite carbamazepine‐10, 11‐epoxide following oral (day 0) and intravenous carbamazepine administration (days 1, 7, and 8). Bioequivalence was evaluated in patients with normal renal function (creatinine clearance >80 ml/min). Safety assessments were conducted through day 38. Results Ninety‐eight patients enrolled and 77 completed the PK component. The mean daily oral and intravenous carbamazepine dosage for 64 PK‐evaluable patients with normal renal function was 962.5 and 675.1 mg (70% of oral dosage), respectively. Steady‐state minimum concentration (Cmin) and overall exposure (AUC0–24) for intravenous carbamazepine infused over 30, 15, or 2–5 min were similar to oral carbamazepine. The 90% confidence intervals (CIs) for the ratios of the adjusted means for AUC0–24, maximum concentration (Cmax), and Cmin were within the 80%–125% bioequivalence range for 30‐min intravenous infusions versus oral administration, but exceeded the upper limit for Cmax for the 15‐min and rapid infusions. All intravenous carbamazepine infusions were well tolerated. Significance Intravenous carbamazepine infusions (70% of oral daily dose) of 30‐, 15‐, and 2‐ to 5‐min duration, given every 6 h, maintained patients' plasma carbamazepine concentrations. Intravenous carbamazepine 30‐min infusions were bioequivalent to oral carbamazepine in patients with normal renal function; rapid infusions were well‐tolerated in this study.